The Nematodes Menace: A Review of Parasitic Species, Transmission Dynamics and Preventive Measures - Amala, K.; Swathi, K.; Krishnaveni, M.; Gowri, R.Shyamala; R.Premalatha; Malakondaiah, Suresh (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This review offers a detailed examination of nematodes, directing specifically on gastrointestinal (GI) nematodes and their consequences for human health. Nematodes, commonly known as roundworms, demonstrate a highly heterogenous groups of multicellular organisms and are responsible for various diseases in humans, particularly in resource-limited settings. The paper explores different types of GI nematodes, their characteristics, symptoms, and transmission pathways, highlighting the significant impacts these parasites can have, such as malnutrition, anemia, and cognitive impairments. Additionally, the manuscript emphasizes the importance of prevention and control strategies, including proper sanitation, personal hygiene, and public awareness, in minimizing the spread of these infections. It discusses the role of anthelmintic medications as a vital part of treatment, while also advocating for a comprehensive approach that incorporates improved living conditions, access to clean water, and health education for effective long-term management of GI nematode infections. Ultimately, this work highlights the necessity for coordinated public health initiatives and ongoing research to alleviate the burdens of GI nematodes and improve health outcomes in at-risk populations.